Effect of sprinkler irrigation method and addition urea fertilizer on wheat plant - R. Al-Awadi; A.I. Ilbas (Овощи России)
Originality/Value: Farmers must use sprinkler irrigation and avoid surface irrigation because it harms the soil and increases its salinity, also represents a waste of water resources.Research limitations: Limited availability of sufficient numbers of sprinkler irrigation devices in Iraq, their high prices, and the lack of experience of farmers to use them.The Purpose of the research is to evaluate the effect of the appropriate irrigation method and the amount of fertilizer specified for urea fertilizer that achieves the best growth for the plant and increase its productivity while avoiding a negative impact on soil properties.Research Method: Two types of irrigation: spraying and flooding, and four mineral fertilization treatments (0. 50.100. 150) kg.ha-1 were used in the work to study the apparent characteristics of wheat and the amount of productivity, using statistical analysis (Gen Stat) and simple correlation coefficient to find strength of association between variables. The experiment was carried out in 2023 at Al-Khatib Farm, located in Al-Numaniyah District, it is bordered to the south by Wasit Governorate, 50 km away, and to the north by Baghdad Governorate,160 km away (Iraq).Results and Discussion. Sprinkler irrigation showed significant differences with the surface irrigation in the length of the spike, number of seed per spike,1000 seed weight, number of spikes per square meter, grain yield kg .ha-1 and the harvest index, while the plant height was not significant. The study also showed that the correlation coefficient between the apparent characteristics of the plants was stronger in the case of using sprinkler irrigation compared to the surface irrigation.